Sonic Cradle; Project Exhibition in Chronic Pain: Art & Science Collaborations - Gromala, Diane; Vidyarthi, K. J.; Riecke, Bernhard E. (2011)
For your cvs, hte citation is: Sonic Cradle (project) Names Title: Chronic Pain: Art & Science Collaborations California Nanosystems Institute (CNSI) UCLA September 29 – November 30, 2011
Keywords: Riecke; Riecke_2011; VR demo; VR exhibition; diane-gromala; jay-vidyarthi; sonic-cradle; talkWithoutPaper